ANALISIS KEBUTUHAN TRAFFIC LIGHT PADA SIMPANG TAMAN KOTA KETAPANG - Anggi Puspita; Nely Kurnila (Journal of Research and Inovation in Civil Engineering as Applied Science, 2023)
The increase in traffic volume is a problem that causes congestion of asection of road, especially on urban roads. The problem of congestion points generally occurs at intersections, which can be found at the intersection of four Jalan Jenderal Sudirman, Jalan Panembahan Bandala, and Jalan Basuki Rahmat which have the potential to cause accidents, queues for traffic jams and delays. The purpose of this study is to find out whether or not it is necessary to install traffic lights at the intersection. The secondary data used are ketapang regency penduduk data and a map of the research location. Primary data were obtained from direct observations in the field through geometric surveys and traffic volume surveys on Thursdays representing weekdays, Saturdays and Sundays representing holidays. Analysis data using MKJI1997. On weekdays, the afternoon capacity value (C) was2,794.13 smp/hour, traffic flow (Q) was 2.376,4 smp/hour, degree of saturation (DS) 0.85, queue opportunity (QP) of 57,40%-29,04%. On Sunday, the afternoon peak with a capacity value (C) of 2,948,14 smp/h, traffic flow(Q) of 2.680,4 smp/hour, degree of saturation (DS) 0.91, queue odds (QP) of 65,53%-33,22%.The results of the analysis at the Ketapang City Park intersection need to be carried out planning for the installation of traffic lights because it has exceeded 750 vehicles/hour for 8 hours which is one of the criteria for installing a traffic light signaling device (APILL).